Pharmacogenetics and antidepressant treatment outcomes in pregnancy: a Danish-population based study - M. Mushtaq; K. Ishtiak-Ahmed; J. Thirstrup; C. Gasse (European Psychiatry, 2022)
Introduction Depression in pregnancy is common and often requires treatment with antidepressant drugs. Most antidepressants are metabolized by the cytochrome P450 system (CYP), in particular CYP2C19 and -2D6, both of which are genetically polymorphic. Additionally, the activity of these enzymes is altered during pregnancy.